Pengaruh Aromaterapi Lavender Terhadap Insomnia Pada Remaja Putri Di Pondok Pesantren Tanwiriyyah Cianjur Tahun 2022 - Audra Fitri Firotika; Irma Herliana; Nurul Ainul Shifa (Lembaga Pengembangan Kinerja Dosen, 2023)
Introduction: Insomnia is a problem or sleep disorder experienced by a person. One non-pharmacological therapy to reduce insomnia is lavender aromatherapy. Objective: The aim of this research is to determine the effect of lavender aromatherapy on the incidence of insomnia in adolescent girls. Method: This research design is quasi-experimental with One-Group Pretest – Posttest Design. The sampling technique used purposive sampling with a total of 17 respondents. Analysis uses the Paired Sample T-test statistical test. Results: The description of insomnia before being given lavender aromatherapy was categorized as mild insomnia by 71% or 12 people. The description of insomnia after being given lavender aromatherapy was categorized as not having insomnia by 88% or 15 people. The results of the study showed that there was an effect of lavender aromatherapy on the incidence of insomnia in young women with a value of p = 0.001 (α < 0.05). Conclusion: From the research results, there is an influence of lavender aromatherapy to reduce insomnia in young women at the Tanwiriyyah Cianjur Islamic Boarding School.